Minat Mengikuti Pelatihan Layanan Konseling Kelompok dengan Pendekatan Realitas Pada Guru BK di Indralaya Ogan Ilir - Asitaria, Asitaria; Sofah, Rahmi (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2022)
Interest is a high desire for something, liking, a person's tendency to pay attention to something that is of interest. Therefore, this study aims to determine the interest of guidance and counseling teachers in participating in group counseling service training with a realityapproach. The subjects involved in this study were 24 guidance and counseling teachers for SMP/MTS and SMA/SMK in Indralaya Ogan Ilir. This study used a quantitative descriptive method, the data was taken using a questionnaire (questionnaire) about the interest of guidance and counseling teachers in participating in group counseling service training with a reality approach. Questionnaires were distributed through a google forms which was shared through a whatsapp groups. Data were analyzed using the percentage formula. The results showed that the interest of guidance and counseling teachers in participating in group counseling service training with a reality approach was in the high category of 25%, medium category 71%, and low category 4%. Based on this research, it can be concluded that guidance and counseling teachers who are interested in participating in group counseling service training with a realityapproach.